2022
DOI: 10.15561/20755279.2022.0103
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and sleep quality in Algerian adults during COVID-19 lockdown

Abstract: Background and Study Aim. There is no doubt that the Coronavirus disease (COVID-19) pandemic, and its related containment measures such as lockdown and social distancing, is affecting physical activity and sleep quality  of the general population worldwide. Algeria, one of the most affected countries in Africa, entered the lockdown on March 9, 2020. Numerous studies have explored the interaction between physical activity and sleep quality showing the effect of physical activity levels on sleep, yet previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[ 68 ] For instance, studies examining children [ 69 ] and adults [ 70 ] reported that there was a recovery in PA levels of children and adults after the lockdown was released; however, this level could not reach the same level before the pandemic. Other topics that attracted the interest of researchers were the way COVID-19 affected PA habits [ 71 , 72 ] and the relationship between COVID-19 based anxiety and sleeping pattern [ 73 , 74 ] and the sample consisted of individuals in childhood period. These studies inquired about how COVID-19 affected PA levels of children, if the PA level of children changed due to the release of lockdown and PA habits and needs of children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 ] For instance, studies examining children [ 69 ] and adults [ 70 ] reported that there was a recovery in PA levels of children and adults after the lockdown was released; however, this level could not reach the same level before the pandemic. Other topics that attracted the interest of researchers were the way COVID-19 affected PA habits [ 71 , 72 ] and the relationship between COVID-19 based anxiety and sleeping pattern [ 73 , 74 ] and the sample consisted of individuals in childhood period. These studies inquired about how COVID-19 affected PA levels of children, if the PA level of children changed due to the release of lockdown and PA habits and needs of children.…”
Section: Discussionmentioning
confidence: 99%